THE USE OF VARIOUS READING STRATEGIES TO GET BETTER UNDERSTANDING AND BE CREATIVE READERS - NINA SUZANNE (Ta'dib, 2015)
Reading is a proses of involving reader’s physics and mental. The purpose of reading is not only to get new information passively but also to comprehend the text actively. In order to get good result in reading, a reader needs to apply various strategies. Kinsella (2000) offers several reading strategies such as PACA, KWL Plus, Outlining, and Concept  Building. Those strategies could be well implemented based on reader’s purpose to read. The ability to apply these strategies could lead someone to be a creative and innovative reader.Key words: Better Understanding, Creative Readers,  Reading strategies